Evaluation of the Implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Policy at the Faculty of Languages, Arts, and Culture: Student Perspectives - Kencana, Bekti Anggi Kuala; Sari, Esti Swatika; Suryaman, Maman; Gang, Huang (CV Sinergi Ilmu dan Publikasi, 2025)
The objective of this study is to examine the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy at the Faculty of Languages, Arts, and Culture, Yogyakarta State University, from the perspective of students. The study adopts a mixed-methods approach, integrating quantitative data collected from questionnaires filled out by 63 participants with qualitative insights obtained from interviews with 2 MBKM lecturers and 2 students who have taken part in the MBKM program. The study investigates students’ understanding, satisfaction, perceived effectiveness, and relevance of the MBKM program, as well as challenges faced during its implementation. Results indicate that students generally understand the MBKM objectives and benefit from enhanced skills, practical experiences, and preparation for the workforce. However, issues such as administrative complexity, limited guidance, and insufficient socialization were identified as significant barriers. The study highlights the need for improved information dissemination, streamlined administrative processes, and stronger institutional support to enhance program effectiveness. The novelty of this study lies in its focus on student perspectives, offering valuable insights into how the MBKM policy impacts educational experiences and identifying actionable recommendations for program improvement. This study contributes to the ongoing evaluation of MBKM, ensuring it aligns with students' needs and institutional objectives in preparing graduates for the 21st-century workforce.